Representation of Cultural Values and Identity in Traditional Rote Ndao Songs as a Basis for Character Education in Elementary Schools - Manafe, Merliana Putri; Karsono, Karsono; Roslan, Roslinawati Mohd (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Globalization has the potential to erode local culture, highlighting the need to integrate local wisdom into character education, one of which is through traditional songs as cultural artifacts containing character values and collective identity. This study aims to map the representation of cultural values and identity in Rote Ndao traditional songs, identify embedded character values, and analyze their potential and challenges for integration into elementary school character education within the framework of the Merdeka Curriculum and the Pancasila Student Profile. Using a Systematic Literature Review (SLR) with the PRISMA protocol, literature searches were conducted in Scopus, Google Scholar, Garuda, and ScienceDirect databases, identifying 253 initial articles. After screening based on inclusion criteria, 28 articles published between 2014–2024 were selected for analysis. The findings reveal that Rote Ndao traditional songs reflect values such as cooperation, environmental respect, community loyalty, and ecological wisdom. These values align with the dimensions of the Pancasila Student Profile. Their integration can enhance contextual learning, student engagement, and cultural identity, although challenges remain in teacher competence, learning resources, and cultural adaptation.